Population Survey and Habitat Assessment of the Estuarine Crocodiles Crocodylus porosus at Samunsam River, Sarawak - Mohd Izwan Zulaini, Abdul Gani; Ruhana, Hassan; Rambli, Ahmad (UNIMAS Publisher, 2024)
This study was conducted to assess the current population density and distribution of crocodile in Samunsam River (SR) as well as to examine their habitat characteristic. A total of 45 crocodiles were observed along SR during the two-night survey. The highest size class spotted during the survey was hatchlings with 18 individuals, followed by ‘Class 2’ (n = 12), Eyes Only (n = 8) and ‘Class 3’ (n = 3). The lowest number of crocodiles sighted was from ‘Class 4’ and ‘Class 5’ with 2 individuals, respectively. No crocodile with size more than 3 m (Class 6) was found during the surveys. High abundance of young crocodiles (66.7%) was recorded, suggesting that the population is in a healthy state. In the present study, the range of crocodile relative density was 1.028 – 1.495 nonhatchling/km and this shows significant increase from previous records i.e. 0.500 non-hatchling/ km in 2014 and 0.841 non-hatchling/km in 2016. The increasing trend is an indication of growing population of the reptile in the river. Crocodiles were well-distributed from estuary until further upstream of SR. Young crocodiles were sighted in close proximity to each other or in clusters, along with the presence of at least one adult, which could be a sign that nesting occurs in these particular areas. SR has a wide range of habitat, starting from sandy beaches in river mouth followed by mangroves forest, nipa palm forest and mixed dipterocarp forest. Anthropogenic interventions were minimal along the river. Selected water quality parameters during this study suggests that SR has optimum condition for crocodile population with salinity ranged from 1 to 23 ppt, pH ranged between 4.90 and 7.25 while water temperature ranged between 27.6 ºC and 29.6 ºC. The findings of this study revealed that the crocodile population in SR is growing, most likely due to favourable habitat and environmental condition as well as minimum human disturbance. This implies that Samunsam Wildlife Sanctuary continues to be the suitable habitat for crocodile and successful in its role as an area specialised for conservation of wildlife and their habitats.